9-10 yaş çocukların sürdürülebilir moda farkındalık düzeylerinin belirlenmesi. - ÇINAR, Pınar (Mehmet Akif Ersoy University Journal of Education Faculty, 2025)
Education given in primary school years lays the foundations of environmental responsibility awareness and enables children to acquire habits of protecting nature and using resources efficiently. Sustainable fashion also emerges as a part of this awareness. Individuals who receive this education at an early age grow up to be individuals who show awareness in conscious consumption areas such as sustainable fashion and make choices in this direction in the future. This contributes to the development of a fashion understanding that supports environmental, social and economic sustainability. In this context, the aim of the research is to determine the awareness level of 9-10 year old children about sustainable fashion and to examine the effect of the education given on this awareness.The study group consists of a total of 117 students studying in the 3rd and 4th grades in a primary school determined in the Serdivan District of Sakarya Province in the 2023-2024 academic year. In order to test the effect of the research in a single group pretest-posttest design, dependent groups t-test was used. As a result of the research, it was observed that children's awareness improved after the education in environmental and social sustainability dimensions. It was determined that they were at a certain level of awareness in the economic sustainability dimension, but there was no significant difference between the pretest and posttest averages after the education. Initiating awareness-raising activities on sustainable fashion at an early age for children can play an important role in achieving long-term sustainability goals.